CLASSIFICATION OF MOUNT KELUD VOLCANO SEISMIC SIGNALS DURING ERUPTION IN NOVEMBER 2007 - Lailatul husna lubis; Ratni Sirait; Miftahul Husnah; Ridwan Yususf Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Classification of mount Kelud volcano seismic signals can be divided into several types, VT-A, VT-B, low frequency, multiphase, and tremor. The analysis by classifying the volcano seismic signal from eruption of Mount Kelud based on the shape of the signal. Data analyzed were starting on 16 to 27 October 2007. The results of volcano seismic signal which recording showed different shapes and were classified according to the type of signal. Each seismic signal recording is grouped according to its shape and the classification results are signaled into VT-A, VT-B, multiphase, low frequency, and tremor.Keywords: Kelud mountain, low frequency, multiphase, signal classification, tremor, VT-A, and VT-B.